Geração de viagens em condomínios residenciais multifamiliares de classe média na Região Metropolitana da Grande Vitória - Ferreira, Pietro Rafael (2013)
This study deals with the data, methodology and resources for obtaining equations that describe the trip generation for Middle Class Multifamiliar Residential Condominiums in Metropolitan Region of Grande Vitória. The study starts from the hypothesis that the middle class residential condominiums in the Metropolitan Region of Grande Vitória generates trips according the same pattern in their cities, in a way that we can establish a statistical model based on both characteristics raised in the field and in secondary data. The equations were defined by multiple linear regressions of variables chosen according to the explanation factor of the model and its ease of obtaining. The number of trips, resulting from the use of the equations obtained was compared with results from consecrated international methodologies. Thus, it was concluded that the trip generation equations obtained for residential condominiums of more than 100 units are presented as best fit model than the international equations for the kind of venture analyzed within the studied region. The equations resulting from this study can be used to quantify travel to any multifamily residential condominium studied in the region that has more than 100 units, besides contributing to the formation of a reliable database for the Brazilian scientific community, can be used in future studies of the area and encouraging work of the same nature in other regions.